Diagnostic Dilemma of Post-abortive Patient with Extensive Uterine and Colonic Necrosis Secondary to Clostridium Perfringens: Case Report at Saint Francis Referral Hospital Ifakara Tanzania - Karuhanga, Theresia. A.; Mayoka, Rashidi; Tekie, Fassil; Muhamed, Tariq S.; Elia, Yeremia N.; Masenga, Isabella; Philbert, Madoshi; Kaale, Sadikiel (Medical Research and Its Applications Vol. 7, 2024)
Post abortive Uterine-colon necrosis secondary to Clostridium perfringens infection is extremely rare of unknown incidence. The most reported cases include abdominal or uterine perforation due to C. perfringes forming visceral necrosis. It is associated with significant morbidity and mortality. The pathogen produces Lecithinase C which is a phospholipase C and it is believed to be involved in the pathologic effects of C. perfringens. Below we present the post incomplete abortion who presented with acute abdominal conditions of which surgical intervention was performed in addition to broad-spectrum antibiotics. Intra-operatively, there was extensive uterine and colonic necrosis and the patient survived but remained with permanent complications of total hysterectomy and lack of colon.